Toward Optimizing Coarse Aggregate Types and Sizes in High-strength Concrete - Hamakareem, Madeh; Muhedin, Daban; Hama Rash, Ahmed; Qadir, Sangar; Khodakarami, Loghman (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The development of very effective coarse aggregate types and sizes can lead to a rapid increase in the production of high strengthconcrete (HSC). This research investigates the effects of five different coarse aggregate types and a range of maximum coarse aggregate sizes on the mechanical properties of concrete through experimental tests and numerical analysis. The workability of fresh concrete is examined using the slump cone test, whereas the mechanical performance of hardened concrete is assessed through compressive strength and splitting tensile strength tests. The experimental results are compared to the predicted results from the codes and design guidelines to assess their predictions. Both coarse aggregate types and sizes show a significant influence on the mechanical properties of HSC performance, especially the compressive strength of HSC, which could be increased on average by 25%. Moreover, the predictions of splitting tensile strength using the ACI 318 and ACI 363 equations are not very accurate, particularly at a high strength range. Therefore, this study develops a new equation for predicting splitting tensile strength based on both experimental test results conducted in this research and a significant amount of data collected from the literature. Evaluation metrics, including R2, RMSE, MAPE, and MAE, demonstrate the superior accuracy of the proposed equation compared to the design guidelines equations. The findings of this research can contribute toward the optimization of aggregate type and size in concrete mix design for enhanced performance and provide valuable insights into the relationship between compressive and splitting tensile strengths in HSC.